2021
DOI: 10.1007/s00148-020-00818-x
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic factors associated with self-protecting behavior during the Covid-19 pandemic

Abstract: Given the role of human behavior in the spread of disease, it is vital to understand what drives people to engage in or refrain from health-related behaviors during a pandemic. This paper examines factors associated with the adoption of self-protective health behaviors, such as social distancing and mask wearing, at the start of the Covid-19 pandemic in the USA. These behaviors not only reduce an individual’s own risk of infection but also limit the spread of disease to others. Despite these dual benefits, uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
147
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(170 citation statements)
references
References 57 publications
(36 reference statements)
16
147
2
5
Order By: Relevance
“…In terms of expenditure levels, we found that being in the middle and upper expenditure levels was protective of contracting COVID-19, which supports evidence from previous studies that low socioeconomic status and expenditure may increase the risk of COVID-19 infection [17,36]. A potential explanation may be the lower compliance of lower-expenditure people in applying protective measures, such as wearing masks, physical distancing, and washing hands [37,38] and the lower immune system of those with a lower socioeconomic status due to higher stress levels and a higher allostatic load, which makes them more susceptible to COVID-19 [39][40][41][42].…”
Section: Discussionsupporting
confidence: 88%
“…In terms of expenditure levels, we found that being in the middle and upper expenditure levels was protective of contracting COVID-19, which supports evidence from previous studies that low socioeconomic status and expenditure may increase the risk of COVID-19 infection [17,36]. A potential explanation may be the lower compliance of lower-expenditure people in applying protective measures, such as wearing masks, physical distancing, and washing hands [37,38] and the lower immune system of those with a lower socioeconomic status due to higher stress levels and a higher allostatic load, which makes them more susceptible to COVID-19 [39][40][41][42].…”
Section: Discussionsupporting
confidence: 88%
“…Although we do not have additional data to explain this finding, it is possible that the greater news coverage of biomedical research during the pandemic has increased individuals' appreciation for this scientific process [11] and increased individuals' interest in participating in research. It also may be possible that some individuals (especially younger adults and those with high incomes [12,13]) have experienced increased scheduling flexibility due to the pandemic (eg, due to cancelled travel and events and restrictions on many leisure-time activities [14]) and thus may have more free time to participate in research.…”
Section: Discussionmentioning
confidence: 99%
“…Bonferroni correction was used to correct for multiple testing on the univariate analyses. To determine if having a history of mask-wearing reduced seropositivity, we constructed a causal diagram based on existing literature and first-hand knowledge of the Lake Central school system and a priori identified gender, age, travel history (as a proxy for risk taking behavior), school type, and role at LCSC as potential confounders to control for in the multivariable logistic regression ( S1 Fig ) [ 6 , 16 19 ]. Finally, backward-stepwise feature elimination was used to identify the features most predictive of seropositivity in a multivariable logistic regression starting with the thirteen categories queried in the survey (threshold p -value of 0.05).…”
Section: Methodsmentioning
confidence: 99%